A formação discursiva escolar : uma análise do funcionamento das relações de contradição e de resistência - Schneider, Débora Cristina (2007)
The present dissertation examines the speech pertaining to school, through the Official Speech of the Colégio Estadual Três Mártires, represented for the Projeto Político Pedagógico, and of the speech of the pupils, represented for interviews with pupils of 3º year of Ensino Médio, to analyze the relations of contradiction and resistance present in the FD Escolar. At a first moment, we discourse on the French Analysis of Speech (AD) that it represents the theoretical line that we adopt in this work. When constructing the panorama of the science of the speech, we present the concept-key of our dissertation that is: the ideology, the speech, interdiscourse and the discourse memory, the Discourse Formation, the subject, the production conditions, silence, the language and the discrimination. These concepts will be of extreme relevance for the analysis of the contradiction, resistance, silence, asubject, domination and fight present in the analyzed speeches. After that, we accomplish through one soon historical retrospect concerning the Brazilian education since the discovery until our days that we permit to evaluate the paper of the education in the current scene. After these theoretical constructions, we develop the analysis of the functioning of the Official Speech of the School, from discourse sequences of relevance whose linguistic marks point for the effects of meaning that they disclose, the way as this speech represents the society, the own school, its directives, its Politician-Pedagogical project, the education and the teacher. The speech of the pupils is analyzed in the last chapter of the dissertation and represents, in many occasions, dissonant positions-subject in relation to the Official Speech, what allows to observe the functioning of relations of contradiction and resistance in the interior of the FD Escolar